The speech act of apologising in Japanese online communication: A corpus-assisted study on the use of gomen in written, computer-mediated settings - Diegoli, Eugenia (East Asian Pragmatics, 2022)
Gomen, the object of analysis in this study, is an informal expression commonly signalled as an apology in Japanese. Drawing from a corpus of online Q&A forums in Japanese compiled by the author, the study demonstrates that the real communicative intent of gomen can be something different from an expression of apology, or indeed can be apologising plus other intentions. First, the article describes the pragmatic functions of gomen in real-life situations. Second, it shows different patterns of speech act realisation with respect to gomen when used as an apologetic device. This argument is developed by analysing multiple linguistic and contextual variables that frequently co-occur with gomen and play a role in the realisation of its pragmatic functions.